The profiles and clinical significance of extraocular muscle-expressed lncRNAs and mRNAs in oculomotor nerve palsy - Wu, Lianqun; Shi, Mingsu; Liang, Yu; Huang, Jiaqiu; Xia, Weiyi; Bian, Hewei; Zhuo, Qiao; Zhao, Chen (Frontiers in Molecular Neuroscience, 2023)
Introduction Oculomotor nerve palsy (ONP) arises from primary abnormalities in the central neural pathways that control the extraocular muscles (EOMs). Long non-coding RNAs (lncRNAs) have been found to be involved in the pathogenesis of various neuroparalytic diseases. However, little is known about the role of lncRNAs in ONP. Methods We collected medial rectus muscle tissue from ONP and constant exotropia (CXT) patients during strabismus surgeries for RNA sequencing analysis. Differentially expressed mRNAs and lncRNAs were revealed and included in the functional enrichment analysis. Co-expression analysis was conducted between these differentially expressed mRNAs and lncRNAs, followed by target gene prediction of differentially expressed lncRNAs. In addition, lncRNA-microRNA and lncRNA-transcription factor-mRNA interaction networks were constructed to further elaborate the pathological changes in medial rectus muscle of ONP. Furthermore, RT-qPCR was applied to further validate the expression levels of important lncRNAs and mRNAs, whose clinical significance was examined by receiver operating characteristic (ROC) curve analysis. Results A total of 618 differentially expressed lncRNAs and 322 differentially expressed mRNAs were identified. The up-regulated mRNAs were significantly related to cholinergic synaptic transmission (such as CHRM3 and CHRND) and the components and metabolism of extracellular matrix (such as CHI3L1 and COL19A1), while the down-regulated mRNAs were significantly correlated with the composition (such as MYH7 and MYL3) and contraction force (such as MYH7 and TNNT1) of muscle fibers. Co-expression analysis and target gene prediction revealed the strong correlation between MYH7 and NR_126491.1 as well as MYOD1 and ENST00000524479. Moreover, the differential expressions of lncRNAs (XR_001739409.1, NR_024160.1 and XR_001738373.1) and mRNAs (CDKN1A, MYOG, MYOD1, MYBPH, TMEM64, STATH, and MYL3) were validated by RT-qPCR. ROC curve analysis showed that lncRNAs (XR_001739409.1, NR_024160.1, and NR_002766.2) and mRNAs (CDKN1A, MYOG, MYOD1, MYBPH, TMEM64, and STATH) might be promising biomarkers of ONP. Conclusions These results may shed light on the molecular biology of EOMs of ONP, as well as the possible correlation of lncRNAs and mRNAs with clinical practice.